Exploiting the Flexibility of District Heating System for Distribution System Operation: Set-Based Characterization and Temporal Decomposition - Chen, Weitao; Wang, Xiaojun; Wei, Wei; Xu, Yin; Wu, Jianzhong (IEEE transactions on sustainable energy, 2025)
The proliferation of distributed renewable resources increases the uncertainty in distribution systems. Coupling the distribution system and district heating system helps leverage the flexibility of thermal storage and thus supports the operation of the electrical grid. This paper proposes a method to characterize flexibility from district heating system via polyhedral sets. First, a recursive robust feasibility condition that ensures heat supply adequacy under uncertain demand is established. Then, stagewise robust feasible sets of thermal storage levels are calculated using a customized projection algorithm. Finally, dynamic bounds of electric heaters are computed by a further projection step. With those dynamic bounds, the electric heaters behave like reducible loads, and the demands in each period are decoupled over time, although the dispatch of thermal storage units must comply with inter-temporal constraints. The proposed method allows the two coupled systems to be operated in a distributed way without forecasts and extensive communications. Numerical simulations on small and practically sized testing systems validate the advantage of the proposed method. On average, the set calculation takes about 8 minutes for the day-ahead problem and 11 seconds for real-time dispatch on a portable laptop, and the prediction-free operation policy has an average optimality gap of 3.6% compared to the hindsight optimum.